A novel Liesegang-patterned mineralized hydrogel drives bone regeneration with microstructure control - Yun Wang; Chao Fang; Li-Bo Mao; Yan-Hui-Zhi Feng; Yu-Feng Meng; Hai-Cheng Wang; Shu-Hong Yu; Zuo-Lin Wang (Materials Today Bio)
Bone regeneration remains a critical challenge in modern medicine. Recent advancements have focused on incorporating hierarchical microstructures into biomaterials to enhance osteogenesis. Mineralized hydrogels, while promising, face limitations in precise microstructure control due to technical complexities. In this study, we present a biomimetic hierarchical structural mineralized hydrogel featuring a Liesegang pattern. In vitro experiments confirm that it significantly promotes the migration and osteogenic differentiation of bone mesenchymal stem cells (BMSCs). In vivo experiments further demonstrate its ability to significantly promote bone regeneration, with newly formed bone closely replicating the hydrogel's architecture. Notably, this hydrogel synthesis strategy eliminates time-consuming fabrication and extensive post-processing, offering a scalable and efficient route for advanced bone-regenerative materials.